Sosialisasi Pentingnya Hak Suara untuk Mengurangi Angka Golput pada Pemilihan Umum di SMA Negeri 7 Denpasar - Nyoman Anggara Putera Krismadhita Saber; I Wayan Sutama (Universitas Teuku Umar, 2026)
Elections are a very important democratic process in the system of government in our country. Through elections, people have the opportunity to elect their representatives who will represent their interests in government. Thus, elections become a very important means of determining the direction of government policy and ensuring that people's interests are well represented. In addition, elections are also a means to strengthen democracy and build people's trust in the system of government. Therefore, every citizen must understand the importance of elections and use their voting rights to elect their representatives. Wise voters are sure to exercise their voting rights in the 2024 election to be held on February 14, 2024. Abstention is an abbreviation for “white faction” or “breakaway faction”, which refers to the attitude or actions of a person who decides not to vote in a general election or other election. In other words, an abstention is when a person chooses not to vote or does not vote for an available candidate in the election. Therefore, voting rights are very important for elections, but many people appreciate the importance of voting rights in elections.